The impacts of risk-management committee characteristics and prestige on efficiency - Wu Y.-C.; Kweh Q.L.; Lu W.-M.; Azizan N.A. (Palgrave Macmillan Ltd., 2023)
Data envelopment analysis; Efficiency; Information management; Insurance; Risk assessment; Risk perception; director prestige; Dynamic network; Insurance companies; Malaysians; Moderating effect; Slacks-based measure models; truncated regression; Risk management